Flow-induced vibrations of a pitching and plunging airfoil. (25th February 2020) - Wang, Z.; Du, L.; Zhao, J.; Thompson, M. C.; Sun, X.
Abstract : Abstract : The flow-induced vibration (FIV) of an airfoil freely undergoing two-degrees-of-freedom (2-DOF) motions of plunging and pitching is numerically investigated as a function of the reduced velocity and pivot location in a two-dimensional free-stream flow. This investigation covers a wide parameter space spanning the flow reduced velocity range of 0<U^* =U/( f_nc)10 and the pivot location range of 0x1, where U is the free-stream velocity, f_n is the natural frequency of the system set equal in the plunge and pitch directions, c is the chord length of the foil and x is the normalised distance of the pivot point from the leading edge. The numerical simulations were performed by employing an immersed boundary method at a low Reynolds number ( Re=Uc/[STIX]x1D708=400, with [STIX]x1D708 the kinematic viscosity of the fluid). Through detailed analyses of the dynamics of the 2-DOF vibrations and wake states, a variety of FIV response regimes are identified, including four regions showing synchronisation or near-synchronisation responses (labelled as S‐I, S‐II, S‐III and S‐IV) and four transition regimes (labelled as T‐I, T‐II, T‐III and T‐IV) that show intermittent, switching or chaotic responses, in the x-U^* space.